A Method for Developing Novel 3D Cornea-on-a-Chip Using Primary Murine Corneal Epithelial and Endothelial Cells - Bai, Jing; Fu, Haojie; Bazinet, Lauren; Birsner, Amy E.; D'Amato, Robert J. (Frontiers in Pharmacology, 2020)
Microfluidic-based organ-on-a-chip assays with simultaneous coculture of multi-cell types have been widely utilized for basic research and drug development. Here we describe a novel method for a primary cell-based corneal microphysiological system which aims to recapitulate the basic functions of the in vivo cornea and to study topically applied ocular drug permeation. In this study, the protocols for isolating and cultivating primary corneal epithelial cells and endothelial cells from mouse inbred strain C57BL/6J were optimized, to allow for the development of a primary-cell based microfluidic 3D micro-engineered cornea. This tissue unit, by overcoming the limitations of 2D conventional cell culture, supports new investigations on cornea function and facilitates drug delivery testing.